Organizing principles of cortical layer 6 - Briggs, Farran (Frontiers in Neural Circuits, 2010)
Neurons in the deepest layer of mammalian cerebral cortex are morphologically and physiological diverse and are situated in a strategic position to modulate neuronal activity locally and in other structures. The variety of neuronal circuits within which layer 6 neurons participate differs across species and cortical regions. However even amidst this diversity, common organizational features emerge. Examination of the anatomical and physiological characteristics of different classes of layer 6 neuron, each specialized to participate in distinct circuits, provides insight into the functional contributions of layer 6 neurons toward cortical information processing.